Quality of Life in Renal Failure Patient Undergoing Hemodialysis (Journal of Hama University, 2020)
Chronic Renal Failure (CRF) is defined as a clinical condition characterized by an irreversible loss of kidney function. Hemodialysis is one of the alternative treatments but causes many changes in the aspects of patient's life which may affect the quality of his life. Therefore, the current study aimed to assess the quality of life in 150 patients with (CRF) that undergo hemodialysis sessions in the Kidney department at the National Hama Hospital, Patients were chosen using the convenience sample method, and data were collected using the WHO quality of life questionnaire. The results showed that the majority of patients in the moderate sample had an average level of quality of life regarding both the physical and psychological dimensions, and they had a good level of quality of life regarding both the social and environmental dimensions. The study recommends to show the Hemodialysis patients the physical problems that one caused by treatment and the methods of managing them, the necessity of providing psychological support to those patients by nursing team, by enhancing positive and supportive social relationships, ensuring a safe and healthy environment for the patient, Further studies regarding the factors that affecting the quality of life of Hemodialysis patients are necessary to develop the ways to improve the level of quality of life.